The Influence Of Education, Income And Financial Socialization On Islamic Financial Literacy Of The Trangkil Community - Indra Sari Ningsih; Iwan Fahri Cahyadi (Jurnal Inovasi Pendidikan Ekonomi, 2025)
This study aims to analyze the influence of education, income, and financial socialization on Islamic financial literacy of the community in Trangkil District, Pati Regency. The method used is descriptive quantitative with a survey approach through questionnaires to 100 respondents. Data were analyzed using multiple linear regression with the help of SPSS. The results show that education and financial socialization have a significant effect on Islamic financial literacy, while income has no significant effect. The coefficient of determination of 63.9% shows that the three variables together are able to explain Islamic financial literacy. The study also found that low financial socialization leads to a lack of public understanding of Islamic financial products. Therefore, it is necessary to increase education and disseminate Islamic financial information massively and evenly by institutions or the government to encourage financial literacy, especially the Trangkil community